Depression and factors impacting quality of life among adults with asthma presence in Nevada - Kahane, Elizabeth D.; Chein, Lung-Chang; Labus, Brian; Bhammar, Dharini M.; Chevalier, Jocy-Anna; Moonie, Sheniz (International Journal Of Community Medicine And Public Health, 2022)
Background: Asthma, a chronic, non-communicable disease has been shown to negatively affect mental health and quality of life among adults. Annually approximately 8% of adult Nevadans report current asthma symptoms and 12.6% report having a lifetime diagnosis. The purpose of this study was to evaluate the association between asthma and depression and explore quality of life factors affecting adult Nevadans with asthma. Methods: Using behavioral risk factor surveillance system (BRFSS) data, this study evaluated the association between self-reported asthma and depression in Nevada using weighted multiple logistic regression. BRFSS asthma call-back survey (ACBS) data were used to determine the frequency and extent of quality of life factors affecting a sub-sample of respondents with asthma. Results: After adjustment, adult Nevadans with current asthma were 3.22 times as likely (95% CI: 2.26-4.58) to be depressed compared to those without asthma. Adult Nevadans with lifetime asthma were 2.6 times as likely (95% CI: 1.88-3.61) to be depressed compared to those without lifetime asthma. ACBS respondents indicated depression (38%), activity limitations (40%), sleep disturbance (26%), missing work or activities (31%), cost-related challenges (20%), healthcare usage (33%), environmental trigger exposure (96%) and severe asthma as indicated by use of oral corticosteroids (5%). The most significant correlations were found between depression, missing work/activities, activity limitation, emergency room /urgent care visits, oral corticosteroid use and reporting cost as a barrier. Conclusions: Asthma presence is associated with depression and negatively affects quality of life among adult Nevadans. A public health approach including education and outreach is critical to reduce the impact of asthma on mental health and quality of life.